NUMERICAL MODELLING OF GAS DYNAMIC STRUCTURES IN SPIRAL GALAXIES - Lugovskiy, A.; Filistov, E. (Одеські астрономічні публікації, 2013)
Observations show that in the global morphology of spiral galaxies appear and form multi-scale features that are embedded in a complex complete picture of the galaxy. The origin and nature of the observed heterogeneity of the global spiral pattern of galaxies are not firmly established at this time. Based on the numerical simulation a possible new mechanism of appearance and formation in the two-armed global spiral galaxies’ morphology of a number of gas-dynamic elements similar to each other in shape and independent in brightness is analyzed. Numerical simulation of unsteady gas-dynamic processes occurring under the influence of an external gravitational field is done. It is shown that as a result of the nonlinear supersonic interaction of occurring spiral formations with the flow of the matter features with hydrodynamic nature are appeared, with modeling results well matching with the observations.